Rebranding the identity of a municipal university as a tool for its promotion - Inna A. Akhyamova; Svetlana A. Pletneva (Управление культурой)
One of the effective tools for promoting a university, expanding visual communication and informing the audience about it in the socio-cultural space is the creation of a corporate identity, expressed in a diverse identity of the organization. For an institution of higher education, it is important to emphasize its uniqueness, originality, direction, content compliance. A single corporate identity style that will reflect the mission and format of the university's activities can become a means of achieving this goal. The identity of the municipal budgetary educational institution of higher education "Yekaterinburg Academy of Contemporary Art" (Institute) (hereinafter EASI, Academy) has various media (souvenirs, printing, navigation, etc.), while its elements are too diverse, sometimes not quite are combined with each other, because they are too diverse. All this makes it very difficult to recognize and promote the university in the socio-cultural space of the city. The purpose of this article is to present a rethinking of the existing corporate identity of a municipal university based on an analysis of analogues, to identify options for updating the corporate identity and examples of identity rebranding.